Chromosome-scale assembly of the African yam bean genome - Waweru, Bernice; Njaci, Isaac; Paliwal, R.; Maranga, M.; Muli, Collins; Murungi, E.; Kaimenyi, D.; Lyimo, B.; Nigussie, H.; Ahadi, B.B.; Assefa, E.; Ishag, H.; et al. (2024)
Genomics-informed breeding of locally adapted, nutritious, albeit underutilised African crops can help mitigate food and nutrition insecurity challenges in Africa, particularly against the backdrop of climate change. However, utilisation of modern genome-assisted crop improvement tools including genomic selection and genome editing for many African indigenous crops is hampered by the scarcity of genomic resources. Here we report on the assembly of the genome of African yam bean (Sphenostylis stenocarpa), a tuberous legume crop that is indigenous to Africa. By combining Nanopore-based assembly with Hi-C scaffolding, we produced a high-quality chromosome-scale assembly with an N50 of 69.5 Mbp. Using transcriptome evidence from Nanopore RNASeq and protein homology evidence from related crops, we predicted and annotated 31,614 putative protein coding genes. We also show how this genome substantially improves anchoring of genetic markers from African yam bean, confirming its significance as a resource for genetic research in African yam bean.